Threat Analysis of the Free Papua Organisation's Separatist Movement Against State Sovereignty - Ulhaq M., Faiq Dhiya; Priyanto; Afifudin, M. (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2025)
The separatist movement of the Free Papua Organization (OPM) is a multidimensional threat to Indonesia's sovereignty, covering military, political, economic and social aspects. This research analyzes the threat posed by the OPM using Barry Buzan's security theory and Henry Prunckun's threat analysis concept, specifically related to Threat Intent and Threat Capability. The research method used is a qualitative approach with descriptive analysis of the strategies implemented by OPM and their impact on national stability. The results showed that the OPM adopted a strategy of armed resistance, propaganda and international diplomacy to gain global recognition. The threat posed not only creates national security instability but also disrupts Indonesia's domestic political policies and diplomatic relations with other countries. In addition, social and economic conditions in Papua are increasingly complex due to the prolonged escalation of the conflict. Addressing this threat requires an integrated security approach that combines military policy, diplomacy and more inclusive socio-economic development. The Indonesian government needs to strengthen international diplomacy to reduce foreign support for separatist movements, while reforming the special autonomy policy to be more effective in improving the welfare of the Papuan people. With a comprehensive and sustainable strategy, Indonesia's stability and sovereignty in Papua can be maintained, while creating conditions that are more conducive to development and peace in the region.